Foaming material with low density and low thermal conductivity and preparation method thereof

By combining polymer foaming, reduced pressure foaming and ice template curing, the shortcomings in the existing foaming materials in terms of density and thermal conductivity are solved, and the preparation of low-density and low-thermal conductivity nanocomposite foam materials are achieved, improving the performance and safety of the materials.

CN119552414APending Publication Date: 2025-03-04QINGDAO UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411875263.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing foaming materials have shortcomings in performance, especially in terms of density and thermal conductivity, and the residue of additives added during foaming will cause harm to the human body.

Method used

Combined with polymer foaming, reduced pressure foaming technology and ice template method to prepare nanocomposite foaming materials, through magnetic stirring, rapid freezing of liquid nitrogen, freeze-thaw cycle and reduced pressure foaming, a one-step transformation from hydrogel to foamed aerogel is achieved, and a low-density and low thermal conductivity foaming is prepared.

Benefits of technology

The preparation of foamed materials with low density and low thermal conductivity was achieved, with a density range of 8 to 73 kg/m3 and a thermal conductivity range of 0.026 to 0.049 W/(m·K). A uniform honeycomb-like pore structure was obtained through nanoparticle enhancement, which improved the performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552414A_ABST
    Figure CN119552414A_ABST
Patent Text Reader

Abstract

The invention discloses a low-density low-thermal-conductivity foam material and a preparation method thereof.The interior of the prepared low-density foam material is of a uniform honeycomb-shaped pore structure and is of an open pore structure, and the foaming ratio is 8-14 times. The preparation method comprises the steps that 1, raw materials are weighed and added into a stirring container; 2, adding a surfactant SDS (Sodium Dodecyl Sulfate), and stirring and blending by magnetic stirring; 3, filling the slurry into a mold, and carrying out freezing and thawing circulation; 4, carrying out reduced pressure foaming and foam curing on the gel sample after the freezing and thawing cycle; and 5, drying the cured foam material to obtain a final foaming sample. The density of the prepared foam sample ranges from 8 kg / m < 3 > to 73 kg / m < 3 >, and the heat conductivity ranges from 0.026 W / (m.K) to 0.049 W / (m.K).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of foaming materials, and in particular to a low-density and low-thermal conductivity foaming material and a preparation method thereof. Background Art

[0002] Foaming is generally done by adding raw materials such as plastics (PVA, PE, EVA, etc.) and rubber (SBR, CR) to additives such as foaming agents or surfactants, and obtaining low-density, high-porosity foamed materials through physical foaming or chemical foaming. This material also has functions such as cushioning, sound absorption, sensing, and adsorption, and is widely used in home appliances, automobiles, industrial insulation, packaging and other fields.

[0003] Compared with other polymer foam materials, pure latex foam products have many shortcomings in performance. In the process of making latex foam products, various compounding agents need to be added to improve the final performance of latex foam products [Ultrasonics Sonochemistry, 2022, 82: 105873.]. Regardless of the foaming method, compounding agents such as vulcanizers, foaming agents, and accelerators are added during the foaming process. If these additives remain in the latex products that are in direct contact, they will cause great harm to the human body.

[0004] Compared with traditional foaming agents to construct pore structures, ice is an environmentally friendly template with very high application advantages. Ice template method through simple low-temperature freezing is one of the most widely used technologies for manufacturing porous materials. It can control the pore morphology by controlling the ice formation in the solute suspension [Advanced Materials, 2020, 32(33): 2001222.]. By fine-tuning the freezing and solute parameters, the ice template can use a simple, controllable process to incorporate pores with adjustable morphological characteristics into various materials. Therefore, ice can be used as a template to produce foam materials with complex structures and component distributions, and the pore structure of the foaming material can be regulated by combining stirring and foaming and decompression foaming processes during the foaming process, thereby improving the overall performance of the foaming material and realizing the green preparation and performance regulation of the foaming material.

[0005] The Chinese patent application with application number CN101050128A discloses an improved method for preparing porous materials by freeze drying, which is characterized by controlling the amount of powder and organic additives added to control the solid content of the slurry, controlling the freezing rate to form a green embryo, and finally sintering to make a porous material. By regulating the microstructure of the porous material, the prepared porous material has an open pore volume of 10-90%, but it still cannot meet the actual demand for foam materials. Summary of the invention

[0006] In view of the problems existing in the above-mentioned prior art, the present invention provides a method for preparing nano-composite foam materials by combining polymer foaming, reduced pressure foaming technology and ice template curing, which can realize a one-step transformation from hydrogel to foaming aerogel, and prepare composite latex porous foam materials without sulfur or promoter, giving them low density and low thermal conductivity, and a foaming ratio of 8-14 times.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] A method for preparing a low-density and low-thermal conductivity foam material comprises the following steps:

[0009] 1) preparing a polyvinyl alcohol aqueous solution, weighing the polyvinyl alcohol aqueous solution, a multi-element performance regulating component and a foaming agent into a stirring container;

[0010] 2) The raw materials in step 1) are subjected to magnetic stirring until the total volume expands to 1.5 to 2.5 times the original volume;

[0011] 3) placing the stirred slurry obtained in step 2) into a mold and rapidly freezing it using liquid nitrogen for 10 to 15 minutes;

[0012] 4) placing the sample rapidly frozen in step 3) in a constant temperature box for thawing;

[0013] 5) placing the sample thawed in step 4) in the freezer layer of the refrigerator for refreezing, and placing the frozen sample in a constant temperature box for thawing again;

[0014] 6) placing the thawed sample in step 5) into a sealed reduced pressure container for reduced pressure foaming to obtain a solidified foam material;

[0015] 7) The solidified foam material in step 6) is placed in a drying device for drying to obtain a low-density and low-thermal conductivity foam material.

[0016] Among them, the multi-performance regulating component in step 1) includes one of carboxylated nitrile latex, NRL (natural rubber latex), PAM (polyacrylamide), SA (styrene-acrylonitrile copolymer), CS (polycarbonate), CNC (cellulose nanocrystals), CNT (carbon nanotubes), and GO (graphene oxide).

[0017] Preferably, the dry ratio of PVA used in step 1) is not less than 30%.

[0018] Preferably, the polyvinyl alcohol used in step 1) is PVA-124, and the foaming agent used is the surfactant sodium dodecyl sulfate.

[0019] Preferably, in step 6), the closed container is decompressed from atmospheric pressure to a vacuum degree of 50-200 Pa within 2-4 min.

[0020] Preferably, the drying method in step 7) is drying in a freeze dryer at -60°C to -50°C for 12 hours, or drying in an oven at 80°C to 120°C for 12 hours.

[0021] In addition, the present application also provides a low-density and low-thermal conductivity foam material, which is prepared by the above-mentioned method for preparing the low-density and low-thermal conductivity foam material.

[0022] The present invention combines the process of polymer foaming with reduced pressure vacuum foaming and ice template curing. Its main feature is that the pre-foamed PVA-based hydrogel is foamed under reduced pressure, and a PVA aqueous solution with a ratio of not less than 30% is used as the continuous phase of the foaming material, and XNBRL plays a role of strengthening and toughening the overall PVA as a dispersed phase. In the entire preparation process, freeze-thaw cycles are the key link in constructing a hydrogel with a rich bubble structure. Liquid nitrogen rapid freezing causes the water in the system to freeze rapidly, while capturing the air introduced by magnetic stirring to form initial bubble nuclei. Subsequent thawing (step four) and refreezing (step five) promote repeated melting and recrystallization of ice crystals, further optimize the distribution and morphology of bubble nuclei, and finally form a hydrogel with a bubble structure inside. At this time, the hydroxyl groups between the polyvinyl alcohol (PVA) molecular chains inside the hydrogel form hydrogen bonds, and the hydroxyl groups on the PVA molecular chains and the carboxyl groups grafted with the carboxyl nitrile latex (XNBRL) also form hydrogen bonds, constructing a stable three-dimensional network structure, giving the foaming gel sample a certain strength, and ensuring that the pore structure is not destroyed during the freeze-thaw cycle. When the decompression foaming operation (step six) is performed, the external pressure decreases rapidly. Since the bubbles are wrapped by the gel, a pressure difference is formed inside and outside the bubbles, causing the gas volume in the bubbles to expand rapidly, and the bubbles grow rapidly. In this process, the pressure reduction not only affects the gas behavior in the bubbles, but also has a multi-faceted effect on the hydrogel system. On the one hand, the boiling point of water inside the gel decreases as the pressure decreases, and the water begins to boil and evaporate. This process absorbs a large amount of heat, causing the temperature of the foaming gel to drop rapidly. When the temperature drops below the freezing point, the water phase changes to ice. This process of water phase change to ice caused by decompression is similar to the drying effect, which will significantly promote the crystallization of PVA. Because under low temperature and low pressure environment, the movement of PVA molecular chains is restricted, and it is easier to arrange to form an ordered crystalline structure, thereby improving the crystallinity of PVA. On the other hand, after drying, the high-crystallinity PVA plays a key stabilizing role in the pore wall structure of low-density foam materials. The presence of the crystalline region increases the rigidity and stability of the pore wall, which can effectively resist external stress and prevent the pore wall from collapsing or deforming. At the same time, the formation of the crystalline structure reduces the free volume of the molecular chain, reduces the water absorption of the material, and further improves the performance of the foam material. Finally, a foamed material with a stable pore structure, low density and low thermal conductivity was obtained. This preparation method achieved effective regulation of the structure and properties of the foam material by cleverly combining freeze-thaw cycles, reduced pressure foaming, and the use of reduced pressure to promote PVA crystallization.

[0023] The beneficial effects of the present invention are as follows:

[0024] The foamed material prepared by the present invention has extremely low density and thermal conductivity. The density of the prepared foam sample ranges from 8 to 73 kg / m 3, the thermal conductivity range is 0.026 to 0.049 W / (m·K). The foamed material prepared by the present invention obtains a uniform honeycomb pore structure after being reinforced and toughened by composite nanoparticles, and is mainly a closed-cell structure with a pore size of 300 to 500 μm. Compared with the prior art, the present invention combines polymer foaming with reduced pressure foaming and ice template curing and is used for the preparation of foamed materials, which can obtain a foamed material with better density and thermal insulation effect, and the foaming ratio of the material is 8 to 24 times. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Optical photograph of the low-density and low-thermal-conductivity XNBRL / PVA foam obtained in Example 2 of the present invention;

[0026] Figure 2 Microscopic photograph of the low-density and low-thermal-conductivity XNBRL / PVA foam obtained in Example 2 of the present invention. DETAILED DESCRIPTION

[0027] In order to enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention is clearly and completely described below in conjunction with the accompanying drawings of the present invention. Based on the embodiments in this application, other similar embodiments obtained by ordinary technicians in this field without making any creative work should all fall within the scope of protection of this application.

[0028] Example 1

[0029] The low-density and low-thermal-conductivity rubber-plastic blended foam material in this embodiment is prepared by the following steps:

[0030] 1. Dissolve PVA-124 at 95°C according to a mass percentage of 10%, and weigh the PVA124 aqueous solution in a stirring container for later use; weigh XNBRL latex with a solid content of 44.46% in a stirring container, and then add SDS with a mass fraction of 50 mg / ml, the dry ratio of the above XNBRL to PVA-124 is 1:9, and the amount of SDS added is 1 ml for every 10 ml of the mixed solution of PVA124 and XNBRL latex;

[0031] 2. The raw materials in step 1 are magnetically stirred in a stirring container so that their total volume expands to twice the total volume of the initially added materials;

[0032] 3. Put the stirred slurry obtained in step 2 into a mold and quickly freeze it in a liquid nitrogen environment for 10 minutes;

[0033] 4. Place the sample that has been quickly frozen in step 3 into a thermostat for thawing. The temperature of the thermostat is set to 30°C and the thawing time is 2 hours.

[0034] 5. Place the sample thawed in step 4 in the freezer layer of the refrigerator for refrozen at a freezing temperature of -20°C for 4 hours and place the frozen sample in a constant temperature box for thawing again; the thawing time is 2 hours;

[0035] 6. Put the sample thawed in step 5 into a sealed decompression container. After continuous decompression for 2 minutes, reduce the sample pressure in the sealed container from atmospheric pressure to 50 Pa to obtain a solidified foam material;

[0036] 7. Place the solidified foam material in step 6 into a freeze dryer and dry for 12 hours to obtain a density of 16 kg / m 3 , a rubber-plastic blended foam material with a thermal conductivity of 0.027W / (m·K).

[0037] Example 2

[0038] The low-density and low-thermal-conductivity rubber-plastic blended foam material in this embodiment is prepared by the following steps:

[0039] 1. Dissolve PVA-124 at 95°C according to a mass percentage of 10%, and weigh the PVA-124 aqueous solution in a stirring container for later use; weigh XNBRL latex with a solid content of 44.46% in a stirring container, and then add SDS with a mass fraction of 50 mg / ml, and the amount of SDS added is 1 ml per 10 ml of the mixed solution of PVA124 and XNBRL latex; the dry ratio of the above XNBRL to PVA-124 is 7:3;

[0040] 2. The added sample in step 1 is magnetically stirred in a stirring container so that its total volume expands to twice the total volume of the initially added material;

[0041] 3. Put the stirred slurry obtained in step 2 into a mold and quickly freeze it in a liquid nitrogen environment for 10 minutes;

[0042] 4. Place the sample that has been quickly frozen in step 3 into a thermostat for thawing. The temperature of the thermostat is set to 30°C and the thawing time is 2 hours.

[0043] 5. Place the sample thawed in step 4 in the freezer layer of the refrigerator for refrozen at a freezing temperature of -20°C for 4 hours and place the frozen sample in a constant temperature box for thawing again; the thawing time is 2 hours;

[0044] 6. Put the sample thawed in step 5 into a sealed decompression container. After continuous decompression for 2 minutes, reduce the sample pressure in the sealed container from atmospheric pressure to 50 Pa to obtain a solidified foam material;

[0045] 7. Place the solidified foam material in step 6 into a freeze dryer and dry for 12 hours to obtain a density of 32 kg / m 3 , a rubber-plastic blended foam material with a thermal conductivity of 0.033W / (m·K).

[0046] like Figure 1 As shown in the figure, the surface of the foamed material looks relatively flat, without obvious holes or cracks. This indicates that its internal structure may be relatively uniform. The uniform texture means that it is foamed uniformly during the production process, which has a great influence on its physical properties (such as cushioning performance, compressive strength, etc.).

[0047] like Figure 2 As shown, the image clearly shows the porous structure inside the foam. The shape of these pores presents a honeycomb pore structure with an average pore size of 370μm and is partially interconnected. This porous structure is a typical feature of polymer foams, and these pores can play a role in reducing weight, enhancing thermal insulation and absorbing energy in the material.

[0048] Example 3

[0049] The low-density and low-thermal-conductivity rubber-plastic blended foam material in this embodiment is prepared by the following steps:

[0050] 1. Dissolve PVA-124 at 95°C according to a mass percentage of 10%, and weigh the PVA-124 aqueous solution in a stirring container for later use; weigh XNBRL latex with a solid content of 44.46% in a stirring container, and then add SDS with a mass fraction of 50 mg / ml, and the amount of SDS added is 1 ml per 10 ml of the mixed solution of PVA124 and XNBRL latex; the dry ratio of the above XNBRL to PVA-124 is 7:3;

[0051] 2. The added sample in step 1 is magnetically stirred in a stirring container so that its total volume expands to 1.5 times the total volume of the initially added material;

[0052] 3. Put the stirred slurry obtained in step 2 into a mold and quickly freeze it in a liquid nitrogen environment for 10 minutes;

[0053] 4. Place the sample that has been quickly frozen in step 3 into a thermostat for thawing. The temperature of the thermostat is set to 30°C and the thawing time is 2 hours.

[0054] 5. Place the sample thawed in step 4 in the freezer layer of the refrigerator for refrozen at a freezing temperature of -20°C for 4 hours and place the frozen sample in a constant temperature box for thawing again; the thawing time is 2 hours;

[0055] 6. Put the sample thawed in step 5 into a sealed decompression container. After continuous decompression for 2 minutes, reduce the sample pressure in the sealed container from atmospheric pressure to 50 Pa to obtain a solidified foam material;

[0056] 7. Place the solidified foam material in step 6 into a freeze dryer and dry for 12 hours to obtain a rubber-plastic blended foam material with a density of 73 kg / m3 and a thermal conductivity of 0.049 W / (m·K).

[0057] Example 4

[0058] The low-density and low-thermal-conductivity rubber-plastic blended foam material in this embodiment is prepared by the following steps:

[0059] 1. Dissolve PVA-124 at 95°C according to a mass percentage of 10%, and weigh the PVA-124 aqueous solution in a stirring container for later use; weigh XNBRL latex with a solid content of 44.46% in a stirring container, and then add SDS with a mass fraction of 50 mg / ml, and the amount of SDS added is 1 ml per 10 ml of the mixed solution of PVA124 and XNBRL latex; the dry ratio of the above XNBRL to PVA-124 is 6:4;

[0060] 2. The added sample in step 1 is magnetically stirred in a stirring container so that its total volume expands to twice the total volume of the initially added material;

[0061] 3. Put the stirred slurry obtained in step 2 into a mold and quickly freeze it in a liquid nitrogen environment for 10 minutes;

[0062] 4. Place the sample that has been quickly frozen in step 3 into a thermostat for thawing. The temperature of the thermostat is set to 30°C and the thawing time is 2 hours.

[0063] 5. Place the sample thawed in step 4 in the freezer layer of the refrigerator for refrozen at a freezing temperature of -20°C for 4 hours and place the frozen sample in a constant temperature box for thawing again; the thawing time is 2 hours;

[0064] 6. Put the sample thawed in step 5 into a sealed decompression container. After continuous decompression for 4 minutes, reduce the sample pressure in the sealed container from atmospheric pressure to 150 Pa to obtain a solidified foam material;

[0065] 7. Place the solidified foam material in step 6 into a freeze dryer and dry for 12 hours to obtain a density of 30 kg / m 3 , a rubber-plastic blended foam material with a thermal conductivity of 0.031W / (m·K).

[0066] Example 5

[0067] This embodiment is a preparation step of a low-density and low-thermal-conductivity composite foam material with GO added:

[0068] 1. Dissolve PVA-124 at 95°C according to a mass percentage of 10%, and weigh the PVA124 aqueous solution in a stirring container for later use; weigh a graphene oxide aqueous dispersion with a solid content of 0.2% in a stirring container, and then add SDS with a mass fraction of 50 mg / ml, and the amount of SDS added is 1 ml per 10 ml of the mixed solution of PVA124 and graphene oxide aqueous dispersion; the dry ratio of GO to PVA-124 is 1:9;

[0069] 2. The sample added in step 1 is magnetically stirred in a stirring container so that its total volume expands to 2.5 times the total volume of the initially added material;

[0070] 3. Put the stirred slurry obtained in step 2 into a mold and quickly freeze it in a liquid nitrogen environment for 10 minutes;

[0071] 4. Place the sample that has been quickly frozen in step 3 into a thermostat for thawing. The temperature of the thermostat is set to 30°C and the thawing time is 2 hours.

[0072] 5. Place the sample thawed in step 4 in the freezer layer of the refrigerator for refrozen at a freezing temperature of -20°C for 4 hours and place the frozen sample in a constant temperature box for thawing again; the thawing time is 2 hours;

[0073] 6. Put the sample thawed in step 5 into a sealed decompression container. After continuous decompression for 2 minutes, reduce the sample pressure in the sealed container from atmospheric pressure to 50 Pa to obtain a solidified foam material;

[0074] 7. Place the solidified foam material in step 6 into a freeze dryer and dry for 12 hours to obtain a density of 8 kg / m 3 , a rubber-plastic blended foam material with a thermal conductivity of 0.026W / (m·K).

[0075] Example 6

[0076] This embodiment is a preparation step of a low-density and low-thermal-conductivity composite foam material with GO added:

[0077] 1. Dissolve PVA-124 at 95°C according to a mass percentage of 10%, and weigh the PVA124 aqueous solution in a stirring container for later use; weigh a graphene oxide aqueous dispersion with a solid content of 0.2% in a stirring container, and then add SDS with a mass fraction of 50 mg / ml, and the amount of SDS added is 1 ml per 10 ml of the mixed solution of PVA124 and graphene oxide aqueous dispersion; the dry ratio of GO to PVA-124 is 1:9;

[0078] 2. The added sample in step 1 is magnetically stirred in a stirring container so that its total volume expands to 1.8 times the total volume of the initially added material;

[0079] 3. Put the stirred slurry obtained in step 2 into a mold and quickly freeze it in a liquid nitrogen environment for 10 minutes;

[0080] 4. Place the sample that has been quickly frozen in step 3 into a thermostat for thawing. The temperature of the thermostat is set to 30°C and the thawing time is 2 hours.

[0081] 5. Place the sample thawed in step 4 in the freezer layer of the refrigerator for refrozen at a freezing temperature of -20°C for 4 hours and place the frozen sample in a constant temperature box for thawing again; the thawing time is 2 hours;

[0082] 6. Put the sample thawed in step 5 into a sealed decompression container. After continuous decompression for 2 minutes, reduce the sample pressure in the sealed container from atmospheric pressure to 50 Pa to obtain a solidified foam material;

[0083] 7. Place the solidified foam material in step 6 into a freeze dryer and dry for 12 hours to obtain a density of 10 kg / m 3 , a rubber-plastic blended foam material with a thermal conductivity of 0.028W / (m·K).

[0084] Example 7

[0085] In this embodiment, NRL is used to replace the carboxyl nitrile latex in Example 2 to prepare a low-density and low-thermal conductivity composite foam material. The remaining preparation steps and process parameters are the same as those in Example 2. The density of the prepared cured foam material is 31 kg / m 3 , thermal conductivity is 0.033W / (m·K).

[0086] Example 8

[0087] In this embodiment, PAM is used to replace the carboxyl nitrile latex in Example 2 to prepare a low-density and low-thermal conductivity composite foam material. The dry ratio of PAM to PVA-124 is 1:9. The remaining preparation steps and process parameters are the same as those in Example 2. The density of the prepared cured foam material is 10 kg / m 3 , thermal conductivity is 0.027W / (m·K).

[0088] Example 9

[0089] In this embodiment, SA is used to replace the carboxyl nitrile latex in Example 2 to prepare a low-density and low-thermal conductivity composite foam material. The dry ratio of SA to PVA-124 is 1:9. The remaining preparation steps and process parameters are the same as those in Example 2. The density of the prepared cured foam material is 8 kg / m3 , thermal conductivity is 0.026W / (m·K).

[0090] Example 10

[0091] In this embodiment, CS is used to replace the carboxyl nitrile latex in Example 2 to prepare a low-density and low-thermal-conductivity composite foam material. The dry ratio of CS to PVA-124 is 1:9. The remaining preparation steps and process parameters are the same as those in Example 2. The density of the prepared cured foam material is 11 kg / m 3 , thermal conductivity is 0.027W / (m·K).

[0092] Embodiment 11

[0093] In this embodiment, CNC is used to replace the carboxyl nitrile latex in Example 2 to prepare a low-density and low-thermal conductivity composite foam material. The dry ratio of CNC to PVA-124 is 1:9. The remaining preparation steps and process parameters are the same as those in Example 2. The density of the prepared cured foam material is 8 kg / m 3 , thermal conductivity is 0.028W / (m·K).

[0094] Example 12

[0095] In this embodiment, CNT is used to replace the carboxyl nitrile latex in Example 2 to prepare a low-density and low-thermal conductivity composite foam material. The dry ratio of CNT to PVA-124 is 1:9. The remaining preparation steps and process parameters are the same as those in Example 2. The density of the prepared cured foam material is 8 kg / m 3 , thermal conductivity is 0.029W / (m·K).

[0096] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing a low-density and low-thermal conductivity foam material, characterized in that: The following steps are involved: 1) preparing a polyvinyl alcohol aqueous solution, weighing the polyvinyl alcohol aqueous solution, a multi-element performance regulating component and a foaming agent into a stirring container; 2) The raw materials in step 1) are subjected to magnetic stirring until the total volume expands to 1.5 to 2.5 times the original volume; 3) placing the stirred slurry obtained in step 2) into a mold and rapidly freezing it using liquid nitrogen for 10 to 15 minutes; 4) placing the sample rapidly frozen in step 3) in a constant temperature box for thawing; 5) placing the sample thawed in step 4) in the freezer layer of the refrigerator for refrozen. The frozen samples were placed in a constant temperature box again for thawing; 6) placing the thawed sample in step 5) into a sealed reduced pressure container for reduced pressure foaming to obtain a solidified foam material; 7) The solidified foam material in step 6) is placed in a drying device for drying to obtain a low-density and low-thermal conductivity foam material. Among them, the multi-performance regulating component in step 1) includes one of carboxylated nitrile latex, NRL, PAM, SA, CS, CNC, CNT, and GO.

2. The preparation method according to claim 1, characterized in that: The dry ratio of PVA used in step 1) is not less than 30%.

3. The preparation method according to claim 1, characterized in that: The polyvinyl alcohol used in step 1) is PVA124, and the foaming agent used is the surfactant sodium dodecyl sulfate.

4. The preparation method according to claim 1, characterized in that: In step 6), the sealed container is decompressed from atmospheric pressure to a vacuum degree of 50-200 Pa within 2-4 minutes.

5. The preparation method according to claim 1, characterized in that: The drying method in step 7) is to dry in a freeze dryer at -60°C to -50°C for 12 hours, or to dry in an oven at 80°C to 120°C for 12 hours.

6. A low-density and low-thermal conductivity foam material, characterized in that: The foam material is prepared by the method for preparing the low-density and low-thermal conductivity foam material according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Modified freeze dehydration method for preparing porous material

    CN101050128A